PEMBERIAN NUTRISI TERBAIK UNTUK OTAK ANAK USIA DINI - Sonita, Sandra; Suryana, Dadan (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT Nutrition for children's brains is a fundamental element for the process of children's brain growth and development. Each person's nutritional needs depend on age, gender and activity level. The nutrition needed by children is not the same as the nutritional needs of adults. Early childhood is in the growth stage so their nutritional needs will increase. The aim of this research is to provide good nutrition for the brain of early childhood. This research method is a literature study. Library research or literature review (literature review, literature research). The results of this research are that providing good nutrition plays a very important role in achieving optimal body growth, including the growth of the child's brain. Conclusion: Providing nutrition is very helpful for the growth and development of the child's brain, because nutrition and the nervous system are interconnected.